Voices From an Empire : A History of Afro-Portuguese Literature - Hamilton, Russell G. (Book collections on Project MUSE., 1975)
The literature of the various regions of Lusophone Africa has received relatively little critical attention compared with that which has been focused on the work of writers in the English- and French- speaking countries of Africa. With the profound change.